Effects of phytase supplementation to reduced-nutrient diets on performance, egg quality, and economic parameters in commercial layers - Roque, Fabricia A; Araújo, Cristiane S S; Moraes, Ulisses R T; Wen, Nick; Garcia, Nury A C R; Gonçalves, Jane C; Granghelli, Carlos A; Leite, Brunna G S; Zorzetto, Priscila S; Araújo, Lúcio F (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Exogenous enzyme supplementation is an effective and cost-saving mechanism for increasing the availability of dietary nutrients by increasing digestion and reducing excretion. Objective: To evaluate the effects of phytase supplementation on performance, egg quality, and economic parameters in commercial laying hens fed reduced-nutrient diets from 70 weeks of age. Methods: Novogen White® commercial laying hens (n=256) were randomly allocated to four treatment groups, with eight replicates of eight hens in each group: PC (positive control): conventional diet not supplemented with phytase; diet with reduced levels (RN) of P (-0.12%), Ca (-0.10%), and ME (-14 kcal/kg), and supplemented with 300 phytase units (FTU/kg; RN300FTU); diet with reduced levels of P (-0.16%), Ca (-0.13%), ME (-18 kcal/kg), CP (-8%), synthetic amino acids (-0.01%), and supplemented with 600 FTU phytase/kg (RN600FTU); and diet with reduced levels of P (-0.18% P), Ca (-0.15%), ME (-20 kcal/kg), CP (-20%), synthetic amino acids (-0.01%), and supplemented with 900 FTU phytase/kg (RN900FTU). Results: The layers fed the RN300FTU diet had 2.68% higher egg production than those fed the PC diet. Egg mass produced by PC- and RN300FTU-fed hens was statistically similar. Eggshell thickness was increased in PC-fed hens. Feed cost for the RN900FTU diet was approximately 9% lower compared with that of the PC diet. Conclusion: The best performance and economic results were achieved when layers were fed a reduced-nutrient diet supplemented with 300 FTU phytase.